Financial Aid for Students with Disabilities, 1998 - American Council on Education, Washington, DC. HEATH Resource Center; American Council on Education, Washington, DC. HEATH Resource Center ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This resource guide provides an overview of student financial aid for students with disabilities. It also discusses the roles and responsibilities of those who play a significant part in the process of providing aid to students with disabilities. It addresses the financial aid application procedure, explains key terminology, and suggests timelines and resources for those individuals seeking financial aid. Specific topics include: (1) the three types of financial aid (grants, loans, and work-employment); (2) federal financial aid; (3) what constitutes the "family contribution"; (4) the cost of attendance; (5) financial need; (6) the financial aid process; (7) the financial aid package; (8) expenses that are considered disability related; (9) how vocational rehabilitation fits into the financial aid process; (10) coordination between the vocational rehabilitation agencies and the financial aid offices; (11) financial aid for graduate study; and (12) other sources for financial assistance, such as Supplemental Security Income, Social Security Disability Insurance, services for disadvantaged students, state programs, and private scholarships. World Wide Web sites that offer information about student financial aid are listed as well as 12 selected resources. A pre-college financial aid checklist is included. (CR)
Availability: HEATH Resource Center, One Dupont Circle N.W., Suite 800, Washington, DC 20036-1193; toll-free telephone: 800-544-3284; telephone: 202-939-9320; fax: 202-833-4760; World Wide Web: http://www.acenet.edu; e-mail: HEATH@ace.nche.edu ($2).
Sponsoring Agency: Department of Education, Washington, DC.
ERIC Note: For 1997 edition, see ED 407 758.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Disabilities; Eligibility; Financial Aid Applicants; Higher Education; Instructional Student Costs; Need Analysis (Student Financial Aid); Noninstructional Student Costs; Parent Financial Contribution; Paying for College; Scholarship Funds; Student Financial Aid; Student Loan Programs; Work Study Programs; Guides, Non-Classroom.